Antibiotic-Loaded Polymethylmethacrylate Beads and Spacers in Treatment of Orthopedic Infections and the Role of Biofilm Formation - van Vugt, Tom A. G.; Arts, Jacobus J.; Geurts, Jan A. P. (Frontiers in Microbiology, 2019)
Polymethylmethacrylate (PMMA) also referred as (acrylic) bone cement is a non-degradable biomaterial that has been used in clinical orthopedic practice for several decades. PMMA can be used in a plain formulation, but is often used in an antibiotic-loaded formulation in (primary and revision) arthroplasty and in treatment of orthopedic infections as prosthetic joint infections (PJI) and chronic osteomyelitis. In treatment of PJIs antibiotic-loaded PMMA is often used as a carrier material for local antibiotic delivery in addition to treatment with systemic antibiotics. In this case, the antibiotic-loaded PMMA is often used as a spacer or as a bead chain. Since the introduction of PMMA as an antibiotic carrier there is a tremendous amount of scientific and clinical papers published, which studied numerous different aspects of antibiotic-loaded PMMA. This paper will review the research regarding basic principles of antibiotic-loaded PMMA as mechanism of action, antibiotic-release capacities, choice of antibiotics and influences on mechanical properties of PMMA. Subsequently, concerns regarding the application of antibiotic-loaded PMMA, biofilm formation, antibiotic resistance and local or systemic toxicity will be discussed. In addition to these subjects, the role of antibiotic loaded PMMA in clinical treatment of PJIs and chronic osteomyelitis is discussed in the final part of this paper.